Differentiating and promoting palliative and hospice services in optimizing end-of-life care: - Inam, Rida; Mehmood, Asim; Kazi, Aqdas (Journal of the Pakistan Medical Association, 2025)
Dear Editor, We write to emphasise the significance of Hospice and Palliative Care (PC) and the necessity of distinguishing between them, as they are often mistakenly regarded as identical. The World Health Organization (WHO) states that PC can be used in conjunction with other treatments meant to extend life in the early stages of terminal illness.[1] PC addresses the physical, mental, social, and spiritual well-being of patients and their families as their life-threatening conditions progress. Improvements in quality of life, advanced care planning, symptom load, patient and caregiver satisfaction, and reduced healthcare utilization are all reliably linked to it. [2] PC was initially created for cancer patients who were near death. WHO statistics show that terminal cancer is responsible for a significantly smaller number of deaths than chronic non-cancer disorders. Although the benefits of PC for non-cancer patients are well established, referrals for non-cancer conditions are typically delayed, and their prevalence remains low. [3] Even though Taiwan has the best Quality of Death Index ranking among Asian nations, less than 20% of non-cancer patients in Taiwan receive palliative care services. [3] Patients with end-stage heart failure, dialysis patients, organ transplant recipients, geriatrics, cystic fibrosis, long-term degenerative neurological disorders, and even newborns can now get palliative care. [2] Hospice is provided solely to patients with terminal illnesses, who have a prognosis of six months or fewer to live and choose to forgo curative treatments in favour of allowing the disease to progress naturally, as per Hui et al.'s conceptual framework for hospice. [1,4] Hospice care offers dying patients with a short prognosis comprehensive, multidisciplinary, team-based palliative care, typically in a setting they feel comfortable with. Hospice programs use an interdisciplinary team of physicians, nurses, social workers, counsellors, priests, home health aides, therapists, and volunteers to provide comprehensive services that are suited to the individual needs of patients and caregivers in order to achieve these goals. [5] Numerous benefits have been linked to hospice care. Patients benefit from enhanced emotional support, while caregivers receive an additional layer of assistance in coping with bereavement and grief. Additionally, hospice is associated with lower healthcare costs, hospitalization rates, acute care and invasive treatment utilization, and overall healthcare consumption. [1,5] PC teams can be based in acute care hospitals, in the community offering PC to patients in their own homes and hospice settings. Regardless of the benefits of PC and how it can be provided to individual patients (i.e., within or outside of hospice), it is reported to be underutilized, owing primarily to physician barriers such as inadequate understanding of palliative care, and uncertainty about the prognosis of the disease. Unfortunately, in Pakistan only few hospitals are providing PC and only one hospice centre. Recognising the significance of these services, our primary objective is to advocate for their promotion in the best interests of patients.